Competências digitais dos tutores on-line em cursos de graduação presencial, híbrido e EaD - Lameza, Jacqueline de Oliveira (2024)
Technology is constantly transforming the various ways of carrying out work. Computers and the internet have enabled working from anywhere, and automation tools have helped to perform tasks more quickly. Information and Communication Technologies (ICTs) are tools that assist in the work environment and are now a reality in the educational field. For educators, possessing proficiency in ICTs has become one of the pillars of teaching, as digital skills facilitate education, reflecting the ability to effectively use digital technologies. Thus, this thesis aims to investigate the digital skills of tutors at a private higher education institution and, specifically, to analyze the initial level of digital competence of tutors based on DigCompEdu, offer a course of prescribed continuing education on digital skills to tutors, analyze the level of digital competence of tutors based on DigCompEdu after the second application and compare it with the results of the initial application, and verify if the prescribed continuing education course alters the level of digital competence of tutors. Such research can be justified by the relevance of digital skills to education. To this end, an action research was conducted with the 12 tutors of a private higher education institution who work as online tutors. The research took place in three stages: initially, tutors underwent a self-assessment of their digital skills through the DigCompEdu Check-in for Higher Education; then, they participated in a prescribed continuing education course focused on digital technologies; and, subsequently, after completing the course, they conducted a second self-assessment for comparison of results. The results of the first stage of assessment of digital skills indicate that tutors have skills in digital technologies, with half of them at the leader/pioneer skill level. Therefore, it is concluded that an appropriate training course can contribute to the development of the digital skills of tutors in distance education